Creative Economic Development of Pesantren - Bawono, Anton (Shirkah: Journal of Economics and Business, 2018)
This article mostly focuses on the values performed by pesantren (Islamic boarding school) in taking influence of creative economics within the community. Three factors observed in this paper mainly but may relate to other variables are embedded traditional values, technological resources and the role of ustadz and kyai engaged in the creative economic process. Taking several pesantren in Java and Yogyakarta as research sites, while conducting multiple regression as technique of analysis, this research shows that aforementioned variables have a positive and significant influence on developing creative economic of pesantren. Creative economic of pesantren largely invites more elaborative research, while this research can be a preliminary contribution to the field of new economic challenges within Islamic society.Keywords: pesantren, creative economics, kyai, ustadz